The Efficacy of Neoadjuvant Gemcitabine and Cisplatin Chemotherapy for cT3N0M0 Upper Tract Urothelial Carcinoma: The Impact of Tumor Location - Kohada, Yuki; Hayashi, Tetsutaro; Takemoto, Kenshiro; Miyamoto, Syunsuke; Babasaki, Takashi; Kobatake, Kohei; Kitano, Hiroyuki; Ikeda, Kenichiro; Goto, Keisuke; Hieda, Keisuke; et al. (Urology Journal, 2024)
Purpose: Upper tract urothelial carcinoma (UTUC) can be divided into renal pelvis tumor (RPT) and ureteral tumor (UT) based on the tumor origin. This study aimed to evaluate the efficacy of neoadjuvant chemotherapy with gemcitabine and cisplatin (NAC-GC) in terms of the pathological outcomes and oncological prognoses in patients with UTUC. We also compared its efficacy between RPT and UT. Materials and Methods: Patients who underwent radical nephroureterectomy for clinical T (cT)3N0M0 UTUC between 1999 and 2021 were included. Patients who underwent NAC-GC and those who did not were included in the NAC-GC and non-NAC-GC groups, respectively. Based on the tumor origin, we divided patients with UTUC into RPT and UT groups. Oncological prognosis was assessed using progression-free survival (PFS) and overall survival. Results: Of 44 patients, 20 (45.5%) and 24 (54.5%) patients were in the NAC-GC and non-NAC-GC groups, respectively. The NAC-GC group had significantly lower pathological T stage and negative lymphovascular invasion (LVI), and a better PFS (p < .05) compared to those in the non-NAC-GC group. Among patients with RPT, the NAC-GC group had significantly negative LVI and better PFS than the non-NAC-GC group (p < .05). In contrast, in patients with UT, the NAC-GC group had no significant difference in pathological outcomes, and no significant difference in oncological prognosis was observed between the NAC-GC and non-NAC-GC groups. Conclusion: NAC-GC improves both pathological outcomes and oncological prognosis in patients with cT3N0M0 UTUC. With regard to tumor location, RPT has better pathological outcomes and oncological prognoses than UT.